Variables relacionadas con componentes actitudinales hacia las tecnologías de la información y la comunicación en estudiantes de psicología (2017)
Although there are studies pointing to some attitudinal differences of university students towards the use of Information and Communication Technologies (ICT) based on their socio-demographic characteristics, there is little research regarding how these variables influence the use of ICT in Psychology students. The aim of this study was to describe attitudinal factors towards ICT in Psychology students of six Chilean universities and identify differences in these factors according to demographic characteristics, knowledge and use of ICT. Participants were 184 Psychology students, aged between 20 and 45 years. The instrument used was a questionnaire of attitudes towards computers, complemented with a set of questions on socio-demographic characteristics and on knowledge and use of ICT. Results show a tendency to manage medium levels of knowledge, as well as a high and medium use of ICT. Attitudes were oriented mainly towards positive aspects. A significant difference between the level of use and knowledge in the attitudinal components was found, but not on sex and age. The results of this study pose the need to maintain a positive attitude of actively incorporating ICT in psychological training.